2009
DOI: 10.1007/s12237-009-9226-0
|View full text |Cite
|
Sign up to set email alerts
|

The Nature and Distribution of Particulate Matter in the Mandovi Estuary, Central West Coast of India

Abstract: Systematic seasonal variations of suspended particulate matter (SPM) along a 44-km transect of the Mandovi estuary reveal that the concentrations of SPM are low at river-end stations, increase generally seaward, and are highest at sea-end stations of the estuary. An estuarine turbidity maximum (ETM) occurs at sea-end stations during June-September when river discharge is high and also in February-May when river discharge is low. These are the two windiest times of year, the former associated with the southwest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 43 publications
2
17
0
1
Order By: Relevance
“…The textural characteristics of the sediments are consistent with biofilms produced by diatoms (Higgins et al, 2003), as reported in studies of both modern (natural) estuaries (Kessarkar et al, 2010;Tolhurst et al, 2003) and laboratory-based experiments Paterson, 1989). Our study found textures that are consistent with reported diatom trails and linkages (Fig.…”
Section: Origin Of Clay Mineral Attachmentsupporting
confidence: 90%
See 2 more Smart Citations
“…The textural characteristics of the sediments are consistent with biofilms produced by diatoms (Higgins et al, 2003), as reported in studies of both modern (natural) estuaries (Kessarkar et al, 2010;Tolhurst et al, 2003) and laboratory-based experiments Paterson, 1989). Our study found textures that are consistent with reported diatom trails and linkages (Fig.…”
Section: Origin Of Clay Mineral Attachmentsupporting
confidence: 90%
“…Biofilm (EPS) bound aggregates of clay particles and freshwater diatoms on sand grains have been reported in marine sediment 27 km from the nearest river mouth, implying that biofilm attachments remain effective during transport from the inner estuary clay coat factory into the marine realm (Kessarkar et al, 2010). A marginal marine, primary origin of claycoated grains has been suggested within the continental slope (sediment gravity flows) and basin plain sediments of the Atoka Formation, Arkoma basin, central USA (Bloch et al, 2002;Houseknecht and Ross, 1992) and west of Shetland, UK (Sullivan et al, 1999).…”
Section: Implications For Clay-coated Sand Grains In Sandstonesmentioning
confidence: 99%
See 1 more Smart Citation
“…4). Two processes appear to control SPM and metal concentrations: (a) the increase of SPM towards downstream can be attributed to the development of estuarine turbidity maximum (ETM) that results in resuspension of bottom sediments (Kessarkar et al 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Quando são parcialmente misturados (fluxo da maré maior ou igual à entrada de água doce), apresentam maior eficiência de retenção, atuando também como armadilhas para os sedimentos costeiros. A eficiência de um estuário na retenção de sedimentos depende das suas taxas de sedimentação e da energia disponível para o transporte (Kessarkar et al, 2010).…”
Section: Estuáriosunclassified